Untranquil recollections : nation building in post-liberation Bangladesh - Sobhan, Rehman (Thousand Oaks ; London : Sage Publications, 2021)
"Rehman Sobhan was directly associated with Bangladesh's liberation struggle. In this memoir, he provides an insightful, first-hand account of the challenges faced by the newly independent Bangladesh in the early years of its existence. This book attempts to capture the unique problems of reconstructing the war-devastated economy while building institutions from ground up for a nation which for 24 years had been run through a highly centralized system of colonial-style governance. Untranquil Recollections gives special attention to the author's involvement, as a Member of the Planning Commission, in addressing the problem of reconstruction while coping with the political challenges associated with building institutions, formulating economic policies and overseeing their implementation. The narrative attempts to identify the economic and political forces that were inimical to the radical direction of the national policy set by Prime Minister Sheikh Mujibur Rahman. The book concludes with a discussion of the dark events leading to Mujibur Rahman's assassination along with his family and his closest political colleagues, which resulted in a change in the regime"--
Contents: Preface
Acknowledgements
Introduction: Untranquil Recollections
First Days in Liberated Bangladesh
My First Exposure to Government
The Political Leadership of the Planning Commission
The Workings of the Planning Commission
Discovering the Political Economy of Policymaking
The Challenge of Delivering in the Five-year Plan
Making the State Effective
The Challenge of Improving the Performance of the Nationalized Sector
My Return to Aid Diplomacy
Laying the Foundations of Indo-Bangladesh Economic Relations
The Gathering Storm
Darkness at Noon: The Last Days of the Bangabandhu Era
Recollections in Tranquility
Includes index.
Gift from Asif Saleh Executive Director , BRAC.
Keywords: Sobhan, Rehman -- Anecdotes; Bangladesh -- History -- 20th century; Bangladesh -- Politics and government; Bangladesh